Thienoguanosine brightness in DNA duplexes is governed by the localization of its ππ* excitation in the lowest energy absorption band. (1st July 2022) - Ciaco, Stefano; Gavvala, Krishna; Greiner, Vanille; Mazzoleni, Viola; Didier, Pascal; Ruff, Marc; Martinez-Fernandez, Lara; Improta, Roberto; Mély, Yves
Abstract: Thienoguanosine (thG) is an isomorphic fluorescent guanosine (G) surrogate, which almost perfectly mimics the natural G in DNA duplexes and may therefore be used to sensitively investigate for example protein-induced local conformational changes. To fully exploit the information given by the probe, we carefully re-investigated the thG spectroscopic properties in 12-bp duplexes, when the Set and Ring Associated (SRA) domain of UHRF1 flips its 5′ flanking methylcytosine (mC). The SRA-induced flipping of mC was found to strongly increase the fluorescence intensity of thG, but this increase was much larger when thG was flanked in 3′ by a C residue as compared to an A residue. Surprisingly, the quantum yield and fluorescence lifetime values of thG were nearly constant, regardless of the presence of SRA and the nature of the 3′ flanking residue, suggesting that the differences in fluorescence intensities might be related to changes in absorption properties. We evidenced that thG lowest energy absorption band in the duplexes can be deconvoluted into two bands peaking at ∼350 nm and ∼310 nm, respectively red-shifted and blue-shifted, compared to the spectrum of thG monomer. Using quantum mechanical calculations, we attributed the former to a nearly pure ππ * excitation localized on thG and the latter to excited states with charge transfer character. The amplitude of thG red-shifted band strongly increased when its 3′ flanking C residue was replaced by an A residue in the free duplex, or when its 5′ flanking mC residue was flipped by SRA. As only the species associated with the red-shifted band were found to be emissive, the highly unusual finding of this work is that the brightness of thG in free duplexes as well as its changes on SRA-induced mC flipping almost entirely depend on the relative population and/or absorption coefficient of the red-shifted absorbing species.